The Relationship of the Production and Demand of Green Catfish (Mystus nemurus) In Sungai Paku Village, Sub-District of Kampar Kiri, District of Kampar, Riau Province - Rima Wardani; Firman Nugroho; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research about the relationship of the production and demand of Green Catfish (Mystus nemurus)was conducted on May, 2018 in Sungai Paku Village, Sub-District of Kampar Kiri, District of Kampar, Riau Province. This research was aimed to find the development of the production and demand, and also its relationship and influence between of the production and demand. The method used was Survey Development Research method. Based on the results of research that the development of demand Green Catfish (Mystus nemurus) show a upward trend and development of the production in fluctuation of Green Catfish, but in 2017 show a downward trend. The relationship of the production and demand is as much as 30%, based on the interval coefficient relations between  two vabiable is low. Ratings point in the table R2 explained that demand for Green Catfish affected as many as 9,1% of the volume of production, this means that if demand for Green Catfis as many as 100 Kg, the production result is only able to meet demand as many as 9 Kg. While the remaining as many as 91 Kg is deficiency the production of caused by factors production not discussed in this case.  Key words:, Green Catfish, Development, Demand, Production.